Eco-Innovations Transition of Agri-food Enterprises Into a Circular Economy - Hamam, Manal; D'Amico, Mario; Zarbà, Carla; Chinnici, Gaetano; Tóth, József (Frontiers in Sustainable Food Systems, 2022)
Eco-innovations that reduce the environmental effect of manufacturing and consumption are seen as critical components of sustainable development and a critical component of the transition to a circular economy. Food systems address the issue of food waste, which is generally acknowledged as a cost to the economy, the environment, and society. Eco-innovations seem to be critical for the food system’s transformation to a more circular model centered on sustainable food production and processing. The goal of this paper was to determine the variables that influenced the introduction of product, process, organizational, and marketing innovations in European Union agri-food enterprises between 2012 and 2014. According to a preliminary analysis of the data, 57.40% of agribusinesses did not implement any form of innovation, which prompted the authors to study the difficulties surrounding innovation development over the three-year reference period. Several key factors emerge as significant influences on the introduction of product innovations (0.055**); contractual requirements as significant influences on the introduction of process innovations (-0.081***); and environmental incentives as significant influences on the introduction of marketing innovations (0.062***). Additionally, product (0.704***) and process (1.051***) innovations tend to have a greater influence on enterprises’ views of circular benefits. The investigation also demonstrates how enterprises and end-users interpret the effect of various forms of innovation differently. Indeed, end-users, in contrast to how enterprises understand it, believe that organizational (0.611***) and marketing (0.916***) innovations are critical in pursuing circular benefits.